Cotidianidad de la adolescente embarazada - Angeles Alzamora, Wendy Yubitsa (2017)
This qualitative research had as object of study the daily life of the pregnant teenager. The theoretical approach is based on concepts of daily life, according to Heller and pregnant teenager according Papalia, Olds y Feldman y Emans y Lufer. We used the creative sensitive method Cabral (1998) and the dynamic calendar, developed in a encounter with 06 participants. The techniques used were: group interview, group discussion and participant observation, associated with reflective critical pedagogy of Freire (1994), based on dialogue. The scenario was the District of Porvenir, Trujillo. For data analysis, discourse analysis was used by Orlandi. The results of the thesis were obtained from the dialogue established between the researchers and the participants, unveiling the following category: Heterogeneity of emotions, actions and commitments; constituted by the subcategories: Experiencing diverse emotions, Taking care of me and my future baby, generating new relations with the family and planning a better future.